The effect of phytoremediation on the reduction of mercury-contaminated water from gold processing using water kale (Ipomoea aquatica Forsk) - Kurniawan, Fitra; Cahyadi, Tedy Agung; Ernawati, Rika (Journal of Earth and Marine Technology (JEMT), 2024)
Gold ore processing is carried out by amalgamation techniques where mercury (Hg) is used as a medium to bind gold which results in water pollution around the processing area, so it is necessary to remediate water. One way in managing mercury-contaminated water is phytoremediation of the use of water kale (ipomoea aquatica forsk) and to help the phytoremediation process, ingredients are needed that can help the growth of water kale in increasing the absorption of Hg concentrations, namely the addition of liquid NPK fertilizer. This study aims to analyze water kale without liquid NPK fertilizer, and use liquid NPK fertilizer against water kale in reducing the concentration of Hg, pH and TSS metals in water. This study used an experimental method with an experimental box (container) consisting of 4 treatments, then an Analysis of Variance (ANOVA) test of 5% and Duncan Multiple Rang Test were carried out. The results showed that liquid NPK fertilizer had an influence on reducing the concentration of Hg, pH and TSS in water. Based on the results of experiments using liquid NPK fertilizer, the best treatment results were obtained in mercury absorption by water kale and reducing Hg concentration in water, namely treatment D (contaminated water + water kale + liquid NPK fertilizer) on the 14th day, as evidenced by a decrease in Hg concentration in water by 0.56 mg / l to 0.00486 mg / l, pH 10.1 to 6.86 and TSS 1695 mg / l to 1 mg / l and an increase in nitrate levels,  Phosphate and potassium in water can accelerate absorption by water kale.